Predictors and Consequences of Faking in Personnel Selection : A Dual-Process Perspective - Dürr, Daniel; Justus Liebig University Giessen (My University, 2019)
The dissertation dealt with the topic of predictors and consequences of faking in personnel selection. In particular, this dissertation addressed three main objectives. It (1) tested how much faking occurs in selection exercises varying in fidelity and identified potential predictors in those exercises, (2) tested a faking model aiming to explain the process underlying the effect of faking on performance evaluations, and (3) identified differential predictors and consequences of faking and honest impression management.
Keywords: Faking; Personalauswahl; Inauthentizität; Beobachtereindruck; Leistung; Faking; selection; inauthenticity; observer impression; performance; ddc:150